Pengembangan Sistem Informasi Pelaporan Pendataan Kependudukan Kabupaten Malang Berbasis Website Dengan Metode Rational Unified Process (RUP) - Hana Nur Hanifah; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Kependudukan dan Pencatatan Sipil of Malang is a government agency that functions for population problems in Malang. In the implementation Dispenduk Capil of Malang has several problems related to the submission of population administration and reporting of population data conducted by the village/kelurahan. Submission of population administration has several problems such as the process of submitting a population administration requiring a relatively long time because the process is quite complicated. This is because the community must go through a series of processes starting from the village/kelurahan, kecamatan level and ending up in the dispenduk capil, the number of queues that occur every day, and the extent of the malang district area can be make long distance to came Dispenduk Capil of malang, so the community must have pay the expensive transportation. The process of reporting population data has several problems, i.e. the absence of uniformity of report formats, which makes it difficult to manage reports and the frequent delays in sending reports. Based on these various problems, the solution that can be applied is to create an information system for reporting population data collection. The system was developed using the Rational Unified Process (RUP) method with the initial phase of inception, elaboration, construction, and transition. The system development process begins with performing requirements analysis, system design and system implementation. Then the system is tested using validation testing, compatibility testing and usability testing. The test results reveal that the system runs according to the requirements and can be easily used by the user.